EPISTEMOLOGI AL-JABIRI DALAM PEMBELAJARAN SAINS PADA ANAK USIA DINI - Nadia Farah Amalia; Fitriyani Fitriyani; Mia Revi Ukhtiani (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
Al-Jabiri, the Muslim thinker of Konteporer, put forward three concepts of epistemologi, namely bayani, irfani and burhani, which became a reference in the science learning curriculum. Researchers discussed its implementation in learning activities aimed at knowing the epistemological picture of Al-Jabiri in early childhood at Wijaya Danu Kindergarten. The method used is descriptive qualitative data collection using observation, interviews and documentation. The results showed that the largest portion that can be taught to children at this stage is that science does not distance children from religion but can get closer in instilling children's creeds through reasonable means.